Hubungan Antara Kadar Fenol Dalam Urin Dengan Kadar Hb, Eritrosit, Trombosit Dan Leukosit (Studi Pada Tenaga Kerja Di Industri Karoseri CV Laksana Semarang) - Mahawati, Eni; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background: The concentration of phenol within urine represent accurate biological indicator of benzene exposure on workers. One of chronic effect of benzene exposure is bone marrow disorder that disturbs hematopoesis system, and causes the decrease of blood component count. The aim of this research was to analyze the correlation between phenol urine concentration and haemoglobin (Hb), erythrocyte,thrombocyte, and leukocyte concentration on workers that exposed to benzene in CV Laksana. Methods:This was an explanatory research. Observation and interview were done with a cross sectional approach. The data include respondent’s characteristics (age, job, work periode, body mass index, the use of personal protection equipment), phenol urine, Hb; erythrocyte; thrombocyte; leukocyte concentration. The data were analyzed by univariate and bivariate with Rank-Spearman correlation test. Results: This research showed that the mean of phenol urine concentration was 20 (± SD 4,519) mg/l and prevalence of benzene toxicity 57,1%. The result of haematological examination shows that the mean of Hb concentration was 14,8 (± SD 0,7) mg/dl, leukocyte 8.072,99 (± SD 1.627,9) cells/ųl, thrombocyte 282.857,1 (± SD 64.389,5) cells/ųl and erythrocyte 4.651.428,6 (± SD 25.403,5) cells/ųl. Most of respondents (60%), age between 21-50 years old, work period 3-25 years, mean of body mass index was 23,4. There were 51,43% respondents who didn’t use personal protective equipment and 97,14% respondents who didn’t use gloves as personal protection equipment. Based on Rank-Spearman correlation test, there was a significant correlation between phenol urine concentration and erythrocyte concentration with p value 0,030 and correlation coefficient -0,368. It means that there was a negative correlation between those two kinds of variables. Other statistical tests for the other variables have no significant correlation. Conclusions: Benzene toxicity levels based on phenol urine concentration still in low  exposure category, erythrocyte count was decreased under normal value, but haemoglobin (Hb); thrombocyte and leukocyte concentration were still normal. Workers, company, and worker department need to handle and prevent of benzene toxicity furthermore. This research should be continued with cohort design. Keyword: phenol, benzene, Haemoglobin (Hb), erythrocyte, thrombocyte, leukocyte